PENERAPAN MODEL PEMBELAJARAN CO-OP CO-OP TERHADAP PRESTASI BELAJAR KOGNITIF MATEMATIKA DITINJAU DARI KECERDASAN EMOSIONAL SISWA SMP (Eksperimen Di Kelas VIII SMP Negeri 1 Parungkuda) - Muharom, Nurma Siti (De Fermat : Jurnal Pendidikan Matematika, 2020)
This research aims to determine the effect of the application of the co-op cop-op learning model on students' cognitive mathematics learning achievement in terms of emotional quotient in VIII class Junior High School 1 of Parungkuda. The population of this study are 298 students. The trial was given to 71 students, 35 students in the experimental class and 36 students in\ the control class. The sampling technique used in this research is simple random sampling. The instruments used in this research were subjective tests and emotional quotient questionnaires. The method of data analysis carried out in this study consisted of two methods, namely Two way Anova with unequal cell lines and a Likert scale to process questionnaire data. The results of the study show that there are differences in student achievement using the co-op co-op learning method and students who use the direct learning method. This shows that the researcher's hypothesis is acceptable. Students with high emotional intelligence and using co-op co-op learning models have the highest marginal values.